The foreign language teacher's role in ICT-supported instruction - Podgoršek, Saša (Sodobna pedagogika, 2019)
The main objective of this paper is to present an in-depth analysis of the conception of the teacher's role in ICT-supported foreign language (FL) instruction among teachers in basic and secondary education. In Slovenia, to date, no studies have been conducted in this research field. Therefore, our study aims to fill this research gap. An online survey was used to explore teachers' beliefs about the change of their role in ICT-supported FL instruction in comparison to their role in traditional instruction. The results of the qualitative and quantitative analyses show that the majority of the participants believed that the role of the teacher as a lecturer and information provider changed to that of a facilitator of student learning and provider of student-centred instruction. A minority of the participants perceived their role first as lecturer; for them, ICT is only a tool with its advantages and disadvantages but with minimal or no influence on the traditional role of the teacher. Even though the majority of the teachers believed that their role had changed, the results do not indicate a major shift in the FL teaching paradigm.
Keywords: IKT; informacijsko-komunikacijska tehnologija; izobraževanje učiteljev; pouk; strokovna usposobljenost; teachers; tuji jeziki; učitelji